Cover Image, Volume 99, Issue 2. (18th December 2018) - Mangan, David; McCleary, Barry V; Culleton, Helena; Cornaggia, Claudio; Ivory, Ruth; McKie, Vincent A; Delaney, Elaine; Kargelis, Tadas
Abstract : The cover image is based on the Research Article A novel enzymatic method for the measurement of lactose in lactose‐free products by David Mangan et al., DOI:10.1002/jsfa.9317 . This cover was supported by Megazyme. Abstract : The cover image is based on the Research Article A novel enzymatic method for the measurement of lactose in lactose‐free products by David Mangan et al., DOI:10.1002/jsfa.9317 . This cover was supported by Megazyme.